2014
DOI: 10.1631/jzus.b1300036
|View full text |Cite
|
Sign up to set email alerts
|

Response of seed tocopherols in oilseed rape to nitrogen fertilizer sources and application rates

Abstract: Tocopherols (Tocs) are vital scavengers of reactive oxygen species (ROS) and important seed oil quality indicators. Nitrogen (N) is one of the most important fertilizers in promoting biomass and grain yield in crop production. However, the effect of different sources and application rates of N on seed Toc contents in oilseed rape is poorly understood. In this study, pot trials were conducted to evaluate the effect of two sources of N fertilizer (urea and ammonium nitrate). Each source was applied to five oilse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Moreover, they suggest the increase of tocopherol is dependent on nitrogen source and on genotype, which complicates the discussion of tocopherol composition and content. In addition, Hussain et al (2014) have confirmed that nitrogen source (ureic or ammonium nitrogen) and application rate may significantly affect alpha-, gamma-and total tocopherols content of rapeseeds oil. Furthermore, total tocopherols content was significantly higher in the 2nd growing period in comparison to the 1st growing period.…”
Section: Tablementioning
confidence: 74%
“…Moreover, they suggest the increase of tocopherol is dependent on nitrogen source and on genotype, which complicates the discussion of tocopherol composition and content. In addition, Hussain et al (2014) have confirmed that nitrogen source (ureic or ammonium nitrogen) and application rate may significantly affect alpha-, gamma-and total tocopherols content of rapeseeds oil. Furthermore, total tocopherols content was significantly higher in the 2nd growing period in comparison to the 1st growing period.…”
Section: Tablementioning
confidence: 74%
“…Both have the same isoprenoid precursor, GGDP, which is synthesized following the MEP pathway [44]. GGDP is also the precursor of others isoprenoid compounds, including tocopherols [45] and phytol (Fig. 1).…”
Section: Effect Of Cds On β-Carotene and Lutein Content Of Green Carrmentioning
confidence: 99%
“…Zheshuang-72 represents low erucic acid seed quality and week winter hardness, while Zheshuang-758 having long life cycle and strong winter hardness properties. Beside these, Zheshuang-72 and Zheshuang-758 genotypes are the dominant cultivars in Zhejiang, China (Guan et al 2012;Hussain et al 2013Hussain et al , 2014.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%